Product-Service Architecture (PSA): toward a Service Engineering perspective in Industry 4.0. Issue 31 (2016) - de S. Dutra, Diogo; Silva, José Reinaldo
Abstract: Service Systems are characterized by its intense collaborative relation with the customer. In fact, the customer gives significant input also in the service providing process which anticipates the proper adaptation to a class of services - which normally appears in the design process as a customer feedback . That is a key issue to export the concept of service to other sector as manufacturing. On the other hand, Cyber-Physical Systems (CPS) and Industry 4.0 extended the limits of conventional discrete manufacturing by improving discrete distribution of production components for one side and also improving collaboration between them - which also means intensify interaction. However, in spite of being an advanced concept, most implementations of CPSs are also attached to the idea of product or to a dynamic processes that can result in a product. That product-oriented approach is being questioned and new proposals emerged, based a manufacturing output that is a mix of products and services. In this paper we revisited this new concept and propose an architecture that is an open and distributed product/service production arrangement, called PSA (Product/service architecture) relying on a cloud system of systems. This architecture could generate different manufacturing arrangements including several adaptations meant to fit a target product/service, not yet addressed by CPS manufacturing arrangement proposals. The architecture applies not just for IT infrastructure, but include hardware and human agents in order to organize product-services value units arranged to intensify the final interaction and product/service delivering. In what follows we briefly present the Product-Service Architecture (PSA) and its basic structure, highlighting topics such as the theoretical support to derive manufacturing plans, that is, a dynamic production process over a base of manufacturing services. The focus in this short paper is towards a design discipline which points for a combination of AI methods (planning and scheduling) and a service interactive interface based on internet services, provided by a design framework called SoftDISS. The claim is that this new discipline would fit better the challenge of designing dynamic manufacturing process in Industry 4.0. This is an on going research, and both PSA architecture and the design framework used to obtain the preliminary results shown in this paper are still in development.